Girls leading the conversation: harnessing the potential of podcasting for informal and project-based learning - Marc T. Sager; Saki Milton; Candace Walkington (Discover Education)
Abstract This study aimed to explore the implementation of project-based learning (PBL) principles in informal STEM education, focusing on the experiences of Underrepresented Racially Minoritized (UUREM) girls during a week-long residential STEM summer camp. Utilizing a single case study design, the researchers investigated how PBL facilitates engagement and understanding of STEM concepts through podcasting activities. Participants engaged in immersive exploration, integrating their research on podcasting and interviewing women in STEM fields. Data were collected from participants’ podcast recordings, scripts, and collaborative chat logs. The study revealed insights into collaboration, creativity, scriptwriting, recording, and editing among student groups. Overall, the findings underscore the importance of fostering teamwork and enhancing students’ creative and technical capabilities in project-based learning environments. Integrating PBL within informal learning environments is crucial for supporting UUREM girls in STEM education. This approach not only fosters engagement but also promotes an inclusive atmosphere where diverse perspectives are valued. The study advocates for the expansion of PBL initiatives in informal learning contexts, emphasizing the importance of diversity and inclusion. By empowering UUREM girls through targeted STEM programs, educators can cultivate a generation of confident and capable learners prepared to thrive in STEM fields.